A política de segurança nacional e desenvolvimento : um projeto da Ditadura Militar para o Território Federal de Roraima (1970-1979) - Silva, Amanda Araújo da (2020)
Due to military civil coup, it was estabilished new economic, social and political period in Brazil. In this scenario, the Amazon region came to be considered as a priority for the national government, particularly in the 1970s, because of geopolitical and economic factors. Based on the politics of National Security and Development doctrine, the new government “legitimized” and upheld itself and with the conductiin on its doctrine, the projects and plans for the Amazon and the Federal Territory of Roraima, had as topic the three bases, development integration and security. According to this fact , the present dissertation has as its main emphasis the National Policy for Security and Development of the Brazilian Military Regime in the Amazon, and specifically in the Federal Territory of Roraima between 1970 and 1979. In order to understand how this policy was implemented in the northern part of the country, observing the external and internal geopolitical factors that inserted itself in the Development Policy of the Militarized State and how its actions influenced the implantation of an infrastructure in the Territory. We emphasize this point for the fact that we have noticed empirically, a high set of development actions managed to the Amazon region and so to the Federal Territory of Roraima. Utilizing a great amount of documents, such as official reports, plans, government records and newspapers, as also a rich bibliographic scope, as a way to provide the objectives of this study. It was possible to verify that this region was identified in the mentality of the Military Government as a region that comes to development based mainly on private sector investimento for national or international companies, following this concept, Roraima was pointed in the geopolitical plans from that time as a great economic route, being this the fact of the political and economic support of this Militarized State in the Federal Territory of Roraima.